Study of the mole external genital organs of Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) - CASTRO-O., LUIS ARMANDO; VALDEZ-C., JORGE (Revista Colombiana de Entomología, 1994)
In this study, a description of the mate external genital organs of the maize weevil Sitophilus zeamais is made and the relations between their parts are established. The parts in the study are of the annular type with a robust penis and a tegmen with an apodeme; the penis have also two apodemes that are united at the basis interceding a sclerite.